Determinants of Choice of Energy in Bush Meat Smoking Preservation Method by Households in Ebonyi State, Nigeria (UNIZIK Journal of Agricultural Economics and Extension, 2024)
Bush meat smoking preservation method and choice of energy source is a function amongst other factors. The study provided empirical evidence on the bush meat smoking preservation method and choice of energy sources among hunting households in Ebonyi State, Nigeria. Eighty households were selected using multistage random sampling techniques. Structured questionnaire and oral interview schedule were used to collect primary data. Percentage responses and multinomial legit models were used to address the objectives of the study. The socioeconomic characteristics of the hunting household result showed that most of the respondents were males, high processing experienced, had more formal education and moderate household size. More so, the types of biomass energy sources for meat smoking by the respondents were wood (90%), charcoal (77.5%), agricultural residues (66.5%) and dung (15%). As well, the determinant to choice of biomass energy was educational level, membership of business organization and years of farming experience in meat processing. The constraints to meat smoking in the study area were seasonality of bush meat (90%) zoonotic connection (85%), scarcity of firewood (67.3%), problem of attack of smoked meat by predators (61.25%) and environmental pollution (70%). There is need to increase households’ access to educational programmers and experienced household members should be encouraged to remain in the business.
Keywords: Bush Meat; Energy Sources; Households Smoking; Hunting